Analysing the relationship between seed security and food security: the case of Chimanimani district, Zimbabwe - Ncube, Bulisani Lloyd (Department of Environmental and Geographical Science, 2021)
Many smallholder farmers in southern Africa rely on crop production as their main livelihood source. However, they often suffer from a lack of appropriate seed as well as high levels of food insecurity. Interventions such as community seed production, seed aid, and input subsidies are used to address these concerns. However, the relationship between seed security and food security has been understudied. This study thus aimed to explore the factors that have an impact on the relationship between seed security and food security. This was done to enhance understanding about the conceptual linkages between the dimensions of seed security, which include availability, access, and utilisation, and those of household-level food security, which include dietary diversity and food consumption. The case study was conducted across two sites in Chimanimani district of Zimbabwe. Methods included both quantitative and qualitative research methodologies. Quantitative data were subjected to statistical analyses while qualitative data were analysed for themes and trends. Results showed the dominant role of informal seed systems in ensuring improved access to affordable and timely seed to smallholder farmers. Informal seed sources were more reliable than formal sources in ensuring that seed was available on time and in closer proximity to households. Seeds sourced informally also showed comparable quality to that from formal sources. The relationship between seed security and food security was shown to be complex and contextual rather than direct or one-directional. Seed security does not necessarily equate to food security, nor does seed insecurity necessarily lead to food insecurity. Although timeliness and proximity of seed affect its availability, these did not directly relate to access to food. Similarly, household assets and income correlated with better food security status, but did not always ensure access to seed. This is because farmers' seed sources were predicated on non-financial factors such as social relations. The quality of farmers' seed was essential in ensuring that adequate food was produced. The thesis argues that the combined factors of seed availability, access and utilisation are essential in ensuring better crop productivity and improved food access. Findings underscore the manner in which household determinants such as assets, farming practices and geographical characteristics, as well as broader contextual factors, affect and influence the relationship between seed and food security. These results imply that interventions such as community seed production, seed aid, and input subsidies do not automatically result in improved seed security and therefore food security. Efforts to enhance seed and food security should be informed by specific household characteristics that take account of wider contextual factors such as climate, as well as socioeconomic and political processes that have a historical influence as well as a continuously evolving effect on farmers' seed and food security.